2004
DOI: 10.1063/1.1782953
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive effect and photochromism in the Fe-doped relaxor ferroelectric crystal Pb(Zn1∕3Nb2∕3)O3-PbTiO3

Abstract: The photorefractive properties of the iron-doped Pb(Zn1∕3Nb2∕3)O3-PbTiO3 (PZN-PT) relaxor ferroelectric single crystals were investigated by two-beam coupling experiments. The Fe:0.01wt%- and the Fe:0.1wt%-doped 0.91PZN-0.09PT single crystals were grown with the flux solution method. The Extinction spectrum, the electro-opric coefficient, the light-induced absorption change, and the photoconductivity were measured in these samples. The maximum gain coefficient reached to 21cm−1, which is about twice as large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The maximum gain coefficient reached as high as 21 cm −1 , which is twice as large as that of undoped PZN-9%PT. It was also found that the grating formation rate decreased with the Fe concentration [399]. Recently, photorefractive properties of the [001] c poled PMN-38%PT single crystal have been investigated by the two-wave mixing method [400].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The maximum gain coefficient reached as high as 21 cm −1 , which is twice as large as that of undoped PZN-9%PT. It was also found that the grating formation rate decreased with the Fe concentration [399]. Recently, photorefractive properties of the [001] c poled PMN-38%PT single crystal have been investigated by the two-wave mixing method [400].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…(1-x)Pb(Zn 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PZN-xPT) single crystals have been found to exhibit outstanding optical properties. [11][12][13][14] It was found that PZN-xPT crystals with the composition near the morphotropic phase boundary (MPB) exhibit very large electro-optic and photoelastic coefficients. 15,16 For PZN-8%PT single crystal poled along h001i direction, c 33 $ 450 pm/V, for PZN-10%PT single crystal, c 33 $ 177 pm/V (k ¼ 632.8 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2003, Optical Society of America; and c: Figure 4 of ref. [55], reproduced with permission. Copyright 2004, American Institute of Physics).…”
Section: Pzn‐pt Single Crystalsmentioning
confidence: 99%
“…a) Gain coefficient and b) grating formation rate change with pump intensity (Figure 5 and 6 of ref. [55], reproduced with permission. Copyright 2004, American Institute of Physics).…”
Section: Pzn‐pt Single Crystalsmentioning
confidence: 99%